Kajian Dampak Penerapan Pendidikan Kewirausahaan dan Edupreneurship kepada Peserta Didik Tingkat SMA Sederajat - HARIANTO, GREDY HENGRAWI (JURNAL EKONOMI PERJUANGAN, 2024)
Indonesia is an archipelagic country with a lot of potential that can be developed. Ironically, with all the natural wealth it possesses, it has yet to produce anything meaningful, especially for the advancement of the economic sector. Unfortunately, that progress has not been felt evenly by the Indonesian people. A study conducted by the International Institute for Management Development (IMD) states that Indonesia still has significant deficiencies in investment levels and talent development. This is also considered one of the reasons for the lack of competitiveness of human resources in Indonesia. Schools, as educational institutions, are required to provide education that can enhance the quality of their graduates so that they can become high-quality future employees. The method in the research uses a systematic literature review, which involves a systematic literature review aimed at collecting secondary data in the form of scientific works, journals, and other relevant sources. The research results show that edupreneurship is important to implement because it has a positive impact on the development of students, particularly their skills as entrepreneurs. The development includes progress in activity, enthusiasm in participating in learning activities, and presenting innovative and creative ideas in entrepreneurship. Students also experience an increase in self-confidence, followed by the emergence of task- and result-oriented skills, a willingness to take risks, and the development of leadership qualities in students.